Prestige and quality – DOAJ: New selection criteria and ongoing developments - Bjørnshauge, Lars (Septentrio Conference Series, 2014)
See video of the presentation. The presentation will highlight the important distinction between prestige and quality of (open access) journals and provide insight in the process and challenges of agreeing on and implementing new inclusion criteria for journals to be listed in the Directory of Open Access Journals as a service covering open access journals from all continents. The questions related to global acceptance of concepts of licenses, author deposit policies, persistent identifiers and long term preservation will be addressed as well.